2017
DOI: 10.15244/pjoes/66175
|View full text |Cite
|
Sign up to set email alerts
|

Functional Traits and Reproductive Allocation Strategy of Conyza canadensis as they Vary by Invasion Degree Along a Latitude Gradient

Abstract: This study aims to determine the functional traits and reproductive allocation (RA) strategy of the invasive plant Conyza canadensis across different invasion degrees along a latitude gradient in China. Invasion degree did not affect the functional traits and RA strategy of C. canadensis significantly. The high proportion of reproductive biomass (allocating approximately 20% of total biomass into reproductive behaviors) of C. canadensis across different invasion degrees can achieve a fitness advantage in broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Field data from four Chinese populations showed that growth performance of C. canadensis can vary substantially among climatic conditions within a small geographical region (Wang et al. ), which might indicate broad adaptive abilities to climatic gradients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Field data from four Chinese populations showed that growth performance of C. canadensis can vary substantially among climatic conditions within a small geographical region (Wang et al. ), which might indicate broad adaptive abilities to climatic gradients.…”
Section: Methodsmentioning
confidence: 99%
“…In some parts of its nonnative range (e.g., China), C. canadensis forms highly dominant stands (Weber et al 2008), but such high impact does not occur in the native ranges nor in most parts of its nonnative ranges (C. Rosche and M. A. Shah, personal observations). Field data from four Chinese populations showed that growth performance of C. canadensis can vary substantially among climatic conditions within a small geographical region (Wang et al 2017), which might indicate broad adaptive abilities to climatic gradients.…”
Section: Study Speciesmentioning
confidence: 99%
“…; Wilson & Pinno ; Wang et al . ,c). More importantly, the successful establishment of one invasive species could create a microenvironment in the invaded ecosystems that might increase the possibility of successful colonisation of subsequent invaders (Flory & Bauer ; Kuebbing et al .…”
Section: Introductionmentioning
confidence: 99%
“…Invasive alien species (IAS) are known to induce distinct variations in both the structure and function of native ecosystems (Powell, Chase, & Knight, ; Vilà et al, ; Wang, Jiang, Liu, Zhou, & Wu, ; Wang, Jiang, Zhou, & Wu, ; Wang, Zhou, Liu, & Xiao, ). IAS and native plant species (natives) share the same habitat and experience similar or even identical environmental selection pressures, but differences in functional traits between IAS and coexisting natives have been suggested as key factors for successful invasions (Gross, Börger, Duncan, & Hulme, ; Hulme & Bernard‐Verdier, , ; van Kleunen, Weber, & Fischer, ).…”
Section: Introductionmentioning
confidence: 99%
“…IAS and native plant species (natives) share the same habitat and experience similar or even identical environmental selection pressures, but differences in functional traits between IAS and coexisting natives have been suggested as key factors for successful invasions (Gross, Börger, Duncan, & Hulme, ; Hulme & Bernard‐Verdier, , ; van Kleunen, Weber, & Fischer, ). Furthermore, an IAS may spread across multiple climate zones (Wang, Zhou, Liu, et al, ; Weber, Sun, & Li, 2008; Yan et al, ). Thus, understanding the differences of functional traits between IAS and coexisting natives in different climate zones is important for an understanding of the mechanisms underlying successful plant invasions.…”
Section: Introductionmentioning
confidence: 99%